Bring NUS back to the table! - Padulosi, S. (European Centre for Development Policy Management, 2017)
NUS, or Neglected and Underutilized Species, are wild, cultivated or semi-domesticated non-commodity crops at the margin of mainstream agriculture. Their contribution to tackling food and nutrition insecurity and climate change vulnerability is huge and can no longer be overlooked. They might not be ‘neglected’ for much longer.